A Prospective Comparative Study of Reamed vs. Unreamed Nailing in Fractures Shaft of Tibia - Choudary, Dinesh (Malaysian Orthopaedic Association, 2012)
ABSTRACT: Background: Although the tibia is one of the most commonly fractured long bones in the body, there are two accepted management techniques: reamed and unreamed nailing. There is not a general consensus as to which technique is more advantageous to the patient. Patients and methods: This was a single centre prospective randomized trial of 38 adults with a tibial shaft fracture who were treated with either reamed or unreamed nailing. Results: Overall fracture healing time was 23 weeks in the reamed group and 25 weeks in the unreamed group. Differences in rate of clinical union, clinical outcome, time for weight bearing and complications in both the groups were not statistically significant. Conclusion: There are no clear indications or contraindications to favour either reamed or unreamed nailing over the other. Technique, fracture union, functional outcome and complications are similar in both groups. Considering the ease of technique application and the decreased operative time, unreamed interlocking nailing has an edge over reamed interlocking nailing. KEY WORDS: Reamed, unreamed, interlocking nailing, fracture shaft of tibia